Miniaturized dual-band Wi-Fi antenna for mobile application - Meor Said, Maizatul Alice; Ang, Wy Ruenn; Misran, Mohamad Harris; Othman, Mohd Azlishah; Suhaimi, Shadia; Hassan, Nurmala Irdawaty; Mohd Bahar, Amyrul Azuan (Human Resource Management Academic Research Society, 2024)
This thesis addresses the growing demand for compact and efficient dual-band Wi-Fi antennas operating at both 2.4 GHz and 5 GHz frequencies. Miniaturized dual-band Wi-Fi antenna for mobile application is a collaboration project between UTeM and Intel to design a compact dual-band antenna in mobile application such as smartphones, tablets, and laptops. The objective of this research is to design and optimize a miniaturized dual-band Wi-Fi antenna, operating at 2.4 GHz and 5 GHz, to meet the requirements of compact electronic devices. The scope of this study encompasses the design, simulation, fabrication, and testing of a meander line antenna for dual-band Wi-Fi applications. Meander line antennas are chosen for their ability to achieve compactness and multiband operation. The methodology involves a comprehensive study of meander line antenna configurations, parametric analysis, and optimization to achieve desired performance metrics. The antenna is fabricated and experimentally tested to validate simulation results and assess real-world performance. Measurements are conducted to evaluate parameters such as return loss, radiation pattern, and antenna gain. The research contributes to the ongoing efforts in antenna design for modern communication systems, addressing the challenges posed by size constraints in emerging electronic devices.